Design and performance of the silicon sensors for the CMS barrel pixel detector - Allkofer, Y; Amsler, C; Bortoletto, D; Chiochia, V; Cremaldi, L; Cucciarelli, S; Dorokhov, A; Hoermann, C; Horisberger, R; Kim, D; Konecki, M; Kotlinski, D; et al. (2008)
The CMS experiment at the (LHC) includes a hybrid silicon pixel detector for the reconstruction of charged tracks and of the interaction vertices. The barrel region consists of n-in-n sensors with 100 × 150 μ m2 cell size processed on diffusion oxygenated float zone silicon. A biasing grid is implemented and pixel isolation is achieved with the moderated p-spray technique. An extensive test program was carried out on the H2 beam line of the CERN-SPS. In this paper we describe the sensor layout, the beam test setup and the results obtained with both irradiated and non-irradiated prototype devices. Measurements of charge collection, hit detection efficiency, Lorentz angle and spatial resolution are presented. © 2007 Elsevier B.V. All rights reserved.